Enhancement of odd nitrogen modifies mesospheric ozone chemistry during polar winter. Issue 23 (8th December 2015) - Verronen, P. T.; Lehmann, R.
Abstract: Energetic particle precipitation (EPP) enhances odd nitrogen (NO x ) in the polar upper atmosphere. Model studies have reported a solar cycle response in mesospheric ozone (O3 ) caused by EPP‐related NO x enhancements which are included by applying a vertical NO x flux at around 80 km. However, it is not clear how O3 can be affected when the main chemical catalyst of odd oxygen (O x = O + O( 1 D) + O3 ) loss in the mesosphere is odd hydrogen (HO x ). Here we use a 1‐D atmospheric model and show how enhanced NO x affects mesospheric chemistry and changes HO x partitioning, which subsequently leads to increase in O x loss through standard HO x ‐driven catalytic cycles. Another, smaller increase of O x loss results from HO x storage in HNO3 during night and its release by daytime photodissociation. Our results suggest that EPP, through NO x enhancements, could have a longer‐term effect on mesospheric HO x and O x in polar winter. Key Points: Mesospheric effects of NO enhancements due to energetic particle precipitation (EPP) are modeled NO enhancement leads to HO repartitioning which increases ozone loss by catalytic HO reactions Energetic particle precipitation could have a longer‐term, wintertime effect on mesospheric ozone